Aquariums and Human–Animal Relations at the Great Barrier Reef - Elias, Ann (Queensland Review, 2021)
In the early twentieth century, great delight in the unique tropical beauty of the Great Barrier Reef, coupled with an opportunistic spirit for commercial development, inspired the commission of eye-catching posters and advertisements by Australian tourist organisations. The aim of this article is to discuss a pictorial device that developed alongside the rise of modern tourist advertising images of Great Barrier Reef – a split-level viewpoint that approximates the effect of looking at the Reef through the glass sides of an aquarium. Building on my earlier research published in 2019 on wildlife photography and the construction of the Great Barrier Reef as a modern visual spectacle, and combining art history with environmental history, this article also turns to coloured advertising lithographs. It argues that split-level visualisations separate human from non-human and elevate the idea of human superiority. With the Great Barrier Reef facing unprecedented ecological pressures, the historical images at the centre of this article are instructive for understanding the deleterious effects of anthropogenic impact, as well as early twentieth-century attitudes towards human–non-human relations.